Limited Legal Assistance As Significant Obstacle To Justice - Kurnia Ali Syarif (Cita konsultindo, 2023)
Limited access to legal aid exacerbates obstacles to justice, because it is easy for justice seekers to gain access to legal aid and can provide objective justice in their implementation. To solve this problem, researchers use normative legal research methods to see and describe the effectiveness of the existence of legal assistance for justice seekers. From the results of the research, it was found that to overcome limited legal aid as an obstacle to justice requires a multi-aspect approach. Several potential solutions that need to be implemented include finding solutions to financial constraints, resolving gaps in knowledge and information about the law, balancing bargaining power that seems unequal, facilitating access to legal aid, and dealing with the complexity of legal procedures.